AB0424 Different Strategies of Low Dose Etanercept in Rheumatoid Arthritis Patients in Sustained Remission. (9th June 2015) - Bernardi, L.; Ometto, F.; Botsios, K.; Punzi, L.; Raffeiner, B.; Doria, A.
Abstract : Background: Several trials have assessed the effectiveness of down-titration compared with continuation of the standard dose in rheumatoid arthritis (RA) patients in remission, in order to reduce dose-dependent long-term adverse effects and prevent overtreatment. Guidelines for the management of RA patients with low dose anti-tumor necrosis factor (TNF) agents during a sustained remission are not currently available. Disease activity-guided dose tapering or discontinuation have been proposed [1]; however, the proportion of patients treated according to these strategies who did not experience relapses and radiographic progression remains elusive. Objectives: Compare the effectiveness of two regimens in RA patients with sustained remission in the real practice setting: A) etanercept (ETN) 25 mg every 7 days (LDE7), B) etanercept 25 mg every 10 days (LDE10). Methods: RA patients with sustained remission, defined as DAS 28 <2.6 and SDAI <3.3 for at least 2 years, following low-dose etanercept (25mg/week), and never switched or swapped treatment were recruited. All patients were proposed to enter in LDE10 regimen (baseline). Non biologic DMARDs and corticosteroids treatments remained unchanged. Visits were at month 1, 3, and every 3 months afterwards. In case of a flare defined according to recent validated DAS28 flare criterion [2] (DAS28 change >1.2) patients went back to LDE7. Data considered were: age, sex, positive RF and ACPA, HAQ, DAS28 and SDAI, non biologic DMARDs, corticosteroid, disease duration, flare rate and total Sharp Score (TSS) progression. Mann-Whitney U test, t-test, Chi-square and Fisher's exact test were used. Results: 87 patients were recruited: 26 patients maintained remission with LDE10 regimen for at least 2 years, 46 patients experienced a disease flare within the first 3 months and went back to LDE7, 15 patients refused to space the dose of ETN and continued LDE7 regimen. Comparing LDE10 success and failure groups, significant associations were found: positive RF and/or ACPA were more frequently in LDE10 (OR 5.27, p=0.02); mean ± DAS28 and SDAI at last follow-up were lower in LDE10 success than in LDE10 failure group: 1, 83±0.24 vs 1.97±0.15, p=0.01, and 2.88 0.34 vs 3.20±0.18, p=0.01 respectively. HAQ between baseline and last follow-up visit improved in LDE10 success group (0.98±0.57 vs 0.65±0.46 p=0.03). No significant differences in flare rate, disease duration, time to remission and use of non biologic DMARDs were observed. Notably, no difference in radiographic progression between the two groups was detected; only 3/87 patients had a variation >0, 5 of TSS, none of those in LDE10 success group. After a mean follow-up of 2.78 years, all the patients in the LDE10 success group maintained the regimen. Conclusions: Patients who maintained remission with LDE7 regimen for at least 2 years, particularly those with negative RF and ACPA, were able to maintain a sustained remission in LDE10 regimen and had no radiographic progression. References: den Broeder AA, et al. Dose REduction strategy of subcutaneous TNF inhibitors in rheumatoid arthritis: the DRESS study. BMC Musculoskelet Disord. 2013 van der Maas A, et al. Construct and criterion validity of several proposed DAS28-based rheumatoid arthritis flare criteria. Ann Rheum Dis. 2013 Disclosure of Interest: None declared